CaClust: linking genotype to transcriptional heterogeneity of follicular lymphoma using BCR and exomic variants - Oksza-Orzechowski, Kazimierz; Quinten, Edwin; Shafighi, Shadi; Kielbasa, Szymon M.; van Kessel, Hugo W.; de Groen, Ruben A. L.; Vermaat, Joost S. P.; Sepulveda Yañez, Julieta Haydee; Navarrete Signorile, Marcelo Alejandro; Veelken, Hendrik; van Bergen, Cornelis A. M.; Szczurek, Ewa (My University, 2024)
Tumours exhibit high genotypic and transcriptional heterogeneity. Both affect cancer progression and treatment, but have been predominantly studied separately in follicular lymphoma. To comprehensively investigate the evolution and genotype-to-phenotype maps in follicular lymphoma, we introduce CaClust, a probabilistic graphical model integrating deep whole exome, single-cell RNA and B-cell receptor sequencing data to infer clone genotypes, cell-to-clone mapping, and single-cell genotyping. CaClust outperforms a state-of-the-art model on simulated and patient data. In-depth analyses of single cells from four samples showcase effects of driver mutations, follicular lymphoma evolution, possible therapeutic targets, and single-cell genotyping that agrees with an independent targeted resequencing experiment.
Keywords: cancer genetics; tumour heterogeneity; statistical methods; follicular lymphoma